Study on Wing Fanning as a Signal of Sexual Response and Courtship Behavior of Bactrocera Papayae - Sofian-Azirun, Mohd; Muttardi, F.A.; Hashim, M.R.; Motior Rahman, M. (Academic Journals, 2011)
A series of experiments was carried out at the Institute of Biological Sciences, University of Malaya to identify wing fanning as an attraction or signal of sexual response and courtship behavior of Bactrocera papayae. Sexual natures such as signal or attraction and courtship behavior were determined through males and females with modified wings and sensory receptors, respectively. Wing fanning was effective to attract female towards male (42 to 48) and vice versa (22 to 25). Sexual attractiveness and signaling by males varied with light intensity. Females were attracted more at 18:20 to 18:55 by frequent wing fanning by males and sharply declined after sunset. Least attraction (10) was observed by females toward males with modified wings compared to males with non modified wings. Similarly, males were less attracted by females with modified sensory receptors. Significantly, weaker sexual response was found when both the aristae and antennae were removed. Mating rate (12 to 14) was reduced significantly by males wing removal and clipping (>50) and wing bases waxed. Modified females mated less than non-modified ones due to the preventive measure of the pheromone receptor. Olfactory signals appear to be more important than acoustic signals in determining whether a female would mate or not. Pheromone along with acoustic receptor modification played a key factor in the success of mating. Acoustic and olfactory signals appear less important when eliminated singly, but combined elimination of olfactory and acoustic signal reduces the mating of females by a greater magnitude. Â© 2011 Academic Journals.